2019
DOI: 10.1016/j.mee.2019.110990
|View full text |Cite
|
Sign up to set email alerts
|

RTN in GexSe1-x OTS selector devices

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…55 Another report on GexSe1-x-based devices showing the observation of RTS in ovonic threshold switching mechanism after the forming process. 56 the high voltage regime of more than 0.6 V. This RTS was more likely to be observed in the early stage of the ON state rather than throughout the ON state. This could be attributed to the competing nature of the two parameters, i.e.…”
Section: Reliability Aspects Of Dm: Device Endurance and Observation Of Random Telegraph Signal (Rts)mentioning
confidence: 87%
See 2 more Smart Citations
“…55 Another report on GexSe1-x-based devices showing the observation of RTS in ovonic threshold switching mechanism after the forming process. 56 the high voltage regime of more than 0.6 V. This RTS was more likely to be observed in the early stage of the ON state rather than throughout the ON state. This could be attributed to the competing nature of the two parameters, i.e.…”
Section: Reliability Aspects Of Dm: Device Endurance and Observation Of Random Telegraph Signal (Rts)mentioning
confidence: 87%
“…In Cu-doped Ge 0.3 Se 0.7 devices, it is suggested that the RTS presence in the device is potentially due to thermally activated movement of Cu species within ionic or redox “double-site traps” . Another report on Ge x Se 1– x -based devices showed the observation of RTS in ovonic threshold switching mechanism after the forming process Figure shows different RTS observed in the DM structure during the ON state of the device under 0.4 V voltage amplitude.…”
Section: Reliability Aspects Of Dm: Device Endurance and Observation ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A surprising result is obtained from the 5 nm CN layer, as despite having a factor of nearly 4 difference in first fire voltage and a factor of 4 difference in thickness, after first fire the threshold voltage differs only by 25%. A possible explanation for this is that the first-fire makes a percolative path of defects that facilitate OTS switching at lower voltages 26 . A thicker layer may have a longer path length but still exhibit a comparable switching voltage.…”
Section: Threshold Voltage Analysismentioning
confidence: 99%